Dampak Pameran Interaktif Microbial-Art dalam Memperkenalkan Mikrobiologi Dasar kepada Masyarakat di Jawa Barat, Indonesia - Nurul Nisa Primadiaty; Safira Prisya Dewi; Shifa Hustima Sahara; Syadza Hanifah (Yayasan Penelitian dan Pengabdian Masyarakat Sisi Indonesia, 2025)
The lack of public understanding of microorganisms is due to limited access to information and a negative reputation among the public. One of the approaches to introduce basic microbiology was through interactive exhibitions, bridging microbiology and art. However, there were few reports on the Indonesia Microbial-Art interactive exhibition. Therefore, this study aims to explore the impact of the fusion microbial art interactive exhibition on the public's basic microbial understanding and to study its potential for long-term implementation. This study was conducted by descriptive qualitative approach using thematic analysis based on two exhibition guest’s testimonials that had been organized by Microartmunity, a community that focuses on fusion art and microbiology. In total, there were 92 participants from various academic backgrounds who gave the testimonials. These testimonials were then categorized into four themes: creativity, education, acceptance, and future expectations. Based on the results, 32% of respondents hoped for the continuation of Microbial Art interactive exhibition, including future exhibitions, workshops, the extended presence of the Microartmunity community, and collaborations with relevant stakeholders. The interactive microbial art exhibition also received a positive response from the public, with a response rate of 26%. It suggests that art had an interesting role in delivering scientific information. The public enthusiasm highlights a huge interest in fusion art-science exhibitions. In conclusion, interactive microbial art exhibitions have the potential to be an educational tool in the future.